Medieval English theatre, Volume forty-one (2019) = Medieval English theatre, Volume 41 (2019) - Carpenter, Sarah ca. 20./21. Jh; Dutton, Elisabeth M. 1972-; Kipling, Gordon ca. 20./21. Jh; Twycross, Meg ca. 20./21. Jh (D.S. Brewer, 2020)
Essays on the performance of drama from the middle ages, ranging from the well-known cycles of York to matter from Iran